Nondestructive testing of an aluminum alloy welded joint based on a mathematical model of the thermal welding process and computer microtomography - Syryamkin, Vladimir I. (Russian journal of nondestructive testing)
Strength control of welded joints is used in many industries. X-ray microtomography as a method of nondestructive testing allows one not only to detect the presence of defects, but also to classify them and assess the size of cracks and noncrack-like defects (pores). This article discusses the nondestructive testing of welded joints of 6061 T6 aluminum alloy using computer micrototomography and a mathematical model of the thermal welding process implemented in ANSYS Workbench. Experimental results of the X-ray microtomograph are presented, and the size of defects in this sample is estimated. The mathematical model allowed us to obtain the thermal histories at which the flaws were formed.